A cytotaxonomic analysis of Chinese Polygonatum (Asparagaceae) species. (25th April 2014) - Zhao, Li‐Hua; Zhou, Song‐Dong; He, Xing‐Jin; Wang, Zhi‐Xin; Peng, Lu
<x xml:space="preserve">Abstract</x> Chromosome numbers and karyotype data of 19 Chinese Polygonatum species generated from 51 populations are presented in this paper. Karyograms of P. cirrhifoliodes, P. gracile, P. hookeri, P. jinzhaiense and P. nodosum are reported for the first time. The chromosome numbers 2n = 28 for P. hookeri and 2n = 60 for P. zanlanscianense are reported for the first time. Satellite chromosomes in the analyzed Polygonatum species can be classified into nine types with respect to the position of secondary constrictions. The occurrence of these types correlates with the infrageneric classification. Karyotypes are bimodal in most Polygonatum species. Polyploidy is common in Polygonatum, and polyploid taxa exhibit higher karyotype asymmetry.